Don't Assume A Can Opener: Confronting Patent Economic Theories with Licensing and Enforcement Reality - Greenspoon, Robert P.; Cottle, Catherine M. (Science and Technology Law Review, 2011)
Many different kinds of entities use the United States patent system, from individual inventors, to start-ups, to patent assertion entities, to massive operating companies. Meanwhile, “reward theory,” “prospect theory,” and “commercialization theory” are three theories intended to explain the justifications for, or social costs and benefits of, a patent system. Yet each theory barely acknowledges what goes on during actual patent acquisition, licensing or enforcement, such as transaction costs and litigation uncertainties. This article considers prior economic analyses of the patent system in this new light – patent economic theories, compared against the types of patent-using entities, compared against the costs and uncertainties of patent acquisition, licensing and enforcement.